RANCANGAN MODEL PEMBELAJAR BLENDED LEARNING PADA PROGRAM PENDIDIKAN BAHASA INGGRIS DI UNIVERSITAS TIMOR INDONESIA - Febronia Lasi; Hery Yanto The (Faculty of teaching training and education, 2018)
AbstrakTulisan ini menyajikan rancangan konseptual pengembangan pembelajaran blended learning mata kuliah Percakapan dan Mendengarkan Bahasa Inggris untuk mahasiswa Program Studi Pendidikan Bahasa Inggris di Universitas Timor (Unimor). Blended learning dianggap sebagai model pembelajaran yang tepat untuk diterapkan di Unimor karena dalam pelaksanaannya memungkinkan adanya perpaduan antara pertemuan tatap muka di kelas dengan komponen-komponen pembelajaran daring. Penggunaan berbagai teknologi daring juga diidentifikasi dengan memperhatikan kebutuhan pemelajar untuk mengembangkan keterampilan sesuai keahlian di bidangnya. Pelaksanaan blended learning dapat mendukung mahasiswa untuk memperoleh kualitas hasil belajar yang lebih baik. Kajian konseptual mengenai pengembangan mata kuliah blended learning ini dimulai dengan memaparkan prinsip-prinsip blended learning yang dapat diterapkan di Unimor, kemudian dilanjutkan dengan identifikasi manfaat pelaksanaannya pada mata kuliah Bahasa Inggris. Rancangan konseptual pada tulisan ini selanjutnya akan digunakan sebagai landasan teori untuk mendukung penelitian pengembangan mata kuliah blended learning Percakapan dan Mendengarkan Bahasa Inggris di Unimor.Ã‚Â Kata Kunci: Blended Learning, Desain Pembelajaran, Bahasa InggrisÃ‚Â THE DESIGN OF THE SPEAKING AND LISTENING BLENDED LEARNING COURSE IN THE ENGLISH LANGUAGE DEPARTMENT OF TIMOR UNIVERSITYÃ‚Â AbstractThis paper is a theoretical framework used to design and develop the blended learning course of Comprehensive Speaking and Listening for the students of the English Language Department in the University of Timor (Unimor). The blended learning is considered the proper learning approach to the learning in Unimor due to the possibility of it to enable the integration of face-to-face class-meeting with the online learning. The use of various online technologies is also being taken into account considering the needs of learners to develop skills related to their field of study. The blended learning implementation in Unimor means to support the students to have quality learning experiences. First, this conceptual paper explains principles of blended learning models that can be applied to the learning process of UnimorÃ¢â‚¬â„¢s students. Following that there is an analysis of the benefits of the implementation of blended learning in teaching and learning English. Further the theoretical framework will be used as the literature review of the developmental study to be conducted in developing the blended learning course Comprehensive Speaking and Listening for the students of UnimorÃ‚Â Keywords: Blended Learning, Learning Design, English Language Learning